Penerapan European Legal Framework Mengenai Rezim Anti Money Laundering (AML) Pada Cryptocurrency Sebagai Upaya Pencegahan Kejahatan Keuangan - Kautsar, Naufal Azis; Hanura, Marten (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
This research analyzes the application of the Anti Money Laundering regime on cryptocurrencies in European Union member countries using international regime theory to analyze how far the anti money laundering regime can accommodate cryptocurrencies which aims to find out that European Union member countries have transposed this regime into their domestic law. The increasingly widespread circulation of cryptocurrencies has become a topic for the global communities, and the emergence of various perspectives on cryptocurrencies. The emergence of this cryptocurrency itself opens the door for criminals because cryptocurrencies trait is anonymous and not supervised by any authorities. The European Union is one of those affected by the circulation of cryptocurrencies. By issuing the AMLD-5 regime through the European Legal Framework, the European Union seeks to accommodate the movement of cryptocurrencies. Through the theory of international regimes on the strength factor and also the scope as an indicator to make domestic law in the member of the European Union’s countries could make their domestic laws in accordance with the AMLD-5 regime.